Professional and non‐professional sources of formula feeding advice for parents in the first six months. Issue 3 (13th January 2020) - Appleton, Jessica; Fowler, Cathrine; Laws, Rachel; Russell, Catherine Georgina; Campbell, Karen J.; Denney‐Wilson, Elizabeth
Abstract: Breastfeeding is beneficial to both the mother and infant, yet many infants are either partially or fully fed with formula milk. Those parents feeding with formula receive less support from professional sources than those breastfeeding and may rely on more non‐professional sources for advice, and this contributes to negative emotional experiences such as guilt. This paper explores the sources of advice for formula feeding, factors associated with using professional or non‐professional sources and compares these sources with those used for breastfeeding advice. A secondary analysis of Australian survey data from 270 mothers was performed. Mothers of six‐month‐old infants participated in an online survey, providing information on advice they received or read about formula feeding and/or breastfeeding from professional and non‐professional sources. A fifth of mothers who were formula feeding did not receive any formula feeding advice from professional sources, and only a small fraction (4.5%) of mothers breastfeeding did not received any breastfeeding advice from professional sources. Compared with those mothers breastfeeding receiving breastfeeding advice, fewer mothers formula feeding receive formula feeding advice from both professional and non‐professional sources. The tin of formula was the most used source of formula advice. Mothers feeding with formula at six months were more likely to have received formula feeding advice from professional sources if they had been fully formula feeding before their infant was under the age of three months. Further research is needed to understand the specific barriers to accessing formula feeding advice and what other factors influence access to formula feeding advice.